Analisis kritis studi privasi dan aksesibilitas hunian pondokan mahasiswa dalam perspektif As-Sunnah - Pandita, Gavra (Maliki Interdisciplinary Journal, 2025)
Privacy and accessibility are essential aspects in student housing design, affecting comfort, psychological well-being, and academic performance. This article reviews the journal “Study on Privacy and Accessibility in Student Boarding Houses from the Perspective of As-Sunnah Values”, which emphasizes integrating Islamic design principles to balance private and public spaces. Analysis indicates that the use of space zoning, architectural elements such as mashrabiya and central courtyards, and harmonious space transitions can support both privacy and social interaction. Furthermore, housing accessibility, including proximity to educational facilities and social integration, significantly contributes to student well-being, especially for international students. This review highlights the importance of student housing design that considers physical, psychological, social, and spiritual dimensions, as well as the relevance of implementing As-Sunnah values in modern student accommodations.